Rewarding compliance with fiscal rules: A proposal for reform of the stability and growth pact - Wolfram F. Richter (EconPol Forum, 2023)
The European Commission has recently published legislative proposals for a reform of the Stability and Growth Pact (SGP). The declared object is to make the economic governance of the EU simpler, improve national ownership, place a greater emphasis on the medium term and strengthen enforcement. However, critics doubt that the proposals are suited to enforce member-state fiscal discipline in the original sense of the SGP. This paper argues in favor of shifting the competence to impose sanctions in the event of non-compliant behavior of member states from the Community to the intergovernmental level. Rewarding compliance rather than penalizing non-compliance makes the shift possible. Such a reform should help to strengthen the accountability for enforcing fiscal discipline, as well as the credibility of sanction threats. The reform would bring the governance framework of the SGP closer to that of the European Stability Mechanism (ESM)
Keywords: 330